Drawing Hobby As a Medium to Manage Stress and Self-development - Hartono, Marcelina (Universitas Ciputra, 2022)
The pandemic has changed many aspects of life; mainly, most activities are carried out from home, starting from school, work, and shopping. Staying at home can reduce the risk of spreading the virus, but staying at home for too long may increase stress. This study is taken from various books and journals on psychology that discuss the relationship between stress and hobbies to relieve stress and as a medium for self-development. One of the hobbies that can be a stress reliever is drawing. There is a strong correlation that drawing can turn a negative quarantine impact into a positive one if the coping methods described are applied correctly. Keywords: Pandemic, Drawing, Hobby, Stress management, Self-development, Art therapy.